COVID-19: Unpacking the low number of cases in Africa - Itai Chitungo; Mathias Dzobo; Mbuzeleni Hlongwa; Tafadzwa Dzinamarira (Elsevier, 2020)
Coronavirus disease 2019 (COVID-19) has infected over nineteen million people globally with over 700 ​000 fatalities as of 9 August 2020. To date, Africa has recorded the least amount of COVID-19 confirmed cases. As of 9 August 2020, Africa has 1, 037, 135 cases compared to 10, 615, 855 in Americas and 3, 061, 264 in Europe. In this piece, the authors unpack the low numbers of laboratory confirmed COVID-19 cases in Africa - is it a case of limited testing capacity due to poor health systems or otherwise?